PERSEPSI MASYARAKAT TERHADAP TRADISI SINAMOT DALAM ADAT PERKAWINAN SUKU BATAK TOBA DI DESA SUKA MAJU KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Sitorus, Nomi Destari; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to uncover the communities perception of the tradition of sinamot in the marriage customs of the Batak Toba, as well as to advance the Kabupaten Rokan Hulu. The number of people in this study are all the leaders of the Batak Toba in the village, as to advance the Kecamatan Rambah. The population of this study was 286 heads of households and the sample in this study was 28 families. Data collection techniques are questionnaires, interviews, observations and documentation. Data analysis with qualitative description. The results showed that data on public perception of the tradition of marriageable sinamot revealed that 48% of respondents strongly agreed (SS), 23% agreed (S), 16% less agreement (KS), 12% disagreed (TS). Based on the benchmarks in the number who answered "Strongly Agree + Agree", this represents 71% in the range of 50.01% to 75% or "good". So that public perception of the tradition of sinamot in the marriage customs of the Batak Toba in the village, as for advancing in the Desa Suka Maju Kecamatan Rambah Kabupaten Rokan Hulu, has a good perception.Key Words: Perception, Community, Marriage, Sinamot